Internationalization process of a company in the natural products sector of Rio Grande do Norte: A case study (Research, Society and Development, 2021)
Currently, several factors drive the internationalization of companies; however, these same factors are permeated by potential risks such as physical and cultural barriers, in addition to the severe competition that exists in the world market. In this context, the present work analyzes and describes how the process of international insertion of a Potiguar company took place in the segment of nuts, dried fruits and oleaginous products with already 10 years’ experience with exports (MERCOSUR countries). The work has a descriptive approach, and an essentially qualitative nature, following the Case Study Methodology. Data collection took place through documentary analysis and structured and semi-structured interviews with the company's CEO. In the documentary analysis, we sought to raise the main theories on internationalization and foreign trade, as well as relevant data from the company and its target market. In the structured interviews, a questionnaire with a Likert-type scale was used in order to quantify subjective aspects of the entrepreneur's experience, based on the main constructs related to the internationalization of companies present in the specialized literature. Through the analysis of the data it was possible to observe that the company is well structured in the strategic, tactical and operational elements related to exports, presenting few structural or strategic gaps. The company has an active and gradual internationalization strategy, aimed at approaching culturally close markets and can serve as a model for other companies in the industry due to its export maturity. It was also possible to point out specific elements for improving the marketing strategies of the company's products and its digital transition strategy.